Functional Capabilities of the Cardiorespiratory System in 15-17 Years-Old Female Students: Kemampuan Fungsional Sistem Kardiorespirasi pada Siswi Berusia 15-17 Tahun - Mohammed J.I. Al-Shammari; Masar Hadi Ismail; Zaman Atiea Sabah, Noor; Hassan Jumaa; Pogrebnyak Tatyana A; Khorolskaya Elena N; Grigorenko Svetlana E. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Physiological adaptation during adolescence is influenced by lifestyle and environmental factors, particularly in urban and rural settings. Understanding cardiorespiratory responses to physical activity is crucial for assessing health reserves in young individuals. Aim of the Study: To evaluate physical development and the functional status of the cardiorespiratory system at rest and after physical load among first-year female medical college students from urban and rural areas. Methodology: The study included female students aged 15–16. Physical development was assessed using somatometry (height, weight, chest circumference) and physiometry methods (vital lung capacity [VC], tidal volume [TV], expiratory reserve volume [ERV], heart rate [HR], and blood pressure [SBP, DBP]). Percentile methods and spirometry were applied to measure external respiration indices. Physical load was induced using G.N. Apanasenko’s squat test. Data were processed statistically using integrative indices (vital index, Erisman index). Results: After loading, HR significantly increased in both groups: from 84.6±2.3 to 130.0±4.6 in group I and from 78.1±2.1 to 134.7±3.4 in group II. SBP and DBP also rose markedly, reaching 150.0±5.0 and 162.0±3.4 mmHg, respectively. Cardiac output (CO) increased to 12.69±0.33 L/min in group I and 12.92±0.25 L/min in group II. VC, TV, and ERV remained largely unchanged, while SpO₂ dropped significantly after loading to 82.7±1.4% and 84.0±1.6% in groups I and II, respectively. Conclusion: Urban and rural students exhibited similar adaptive patterns, with rural students showing slightly better oxygen saturation and CO response, suggesting higher functional reserves and greater cardiorespiratory adaptability under physical stress.Highlight : Heart rate and blood pressure rose significantly after physical load. Oxygen saturation dropped, more stable in rural students. Rural students showed better functional reserves and adaptability Keywords : Female Students, Heart Rate, Blood Pressure, Cardiorespiratory System, Physical Activity